THE EFFECT OF THE USE OF BIG BOOK WRITING MEDIA ON STUDENTS' WRITING ABILITY - Zunidar Zunidar (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Learning requires media in bridging the messages conveyed by educators to students. One type of media that is commonly used in the learning process at the elementary age stage is big book writing media. This study aims to determine how the effect of using big book writing media on students' writing skills. The background of the research is at MIN Medan Tembung which is located at Jalan Pertiwi Ujung, Medan, North Sumatra. The type of this research is quantitative with Quasi Experiment method. The population of the data is 40 students (class VA and class VB), with a test instrument in the form of essay questions as many as 10 questions (pre-test and post-test). The results of this study found that (1) big book writing media made students interested in participating in the learning process, dared to express opinions, and played an active role during the learning process; and (2) Based on the average post test results, the use of big book media on the ability to write stories has better writing skills. Based on the t statistical test in the post test, it was obtained that tcount > ttable, 2.689> 2.024 (n = 20) with a significant level of 0.05 or 5% which stated that Ha was accepted and Ho was rejected, it can be concluded that the use of big book media in learning has an influence which has a significant effect on the ability to write stories in the Indonesian subject of fifth grade students at MIN Medan Tembung.